Unrealistic parental expectations for cure in poor‐prognosis childhood cancer. Issue 2 (4th October 2019) - Mack, Jennifer W.; Cronin, Angel M.; Uno, Hajime; Shusterman, Suzanne; Twist, Clare J.; Bagatell, Rochelle; Rosenberg, Abby; Marachelian, Araz; Granger, M. Meaghan; Glade Bender, Julia; Baker, Justin N.; Park, Julie; et al.
Abstract : Background: Many parents of children with advanced cancer pursue curative goals when cure is no longer possible. To the authors' knowledge, no pediatric studies to date have prospectively evaluated prognosis communication or influences on decision making in poor‐prognosis childhood cancer. Methods: The authors conducted a prospective cohort study at 9 pediatric cancer centers that enrolled 95 parents of children with recurrent or refractory, high‐risk neuroblastoma (63% of those who were approached), a condition for which cure rarely is achieved. Parents were surveyed regarding the child's likelihood of cure; their primary goal of care; the child's symptoms, suffering, and quality of life; and regret concerning the last treatment decision. Medical records identified care and treatment decisions. Results: Only 26% of parents recognized that the chance of cure was <25%. When asked to choose a single most important goal of care, approximately 72% chose cure, 10% chose longer life, and 18% chose quality of life. Parents were more likely to prioritize quality of life when they recognized the child's poor prognosis ( P = .002). Approximately 41% of parents expressed regret about the most recent treatment decision. Parents were more likely to experience regret if the child had received higher intensity medical care (odds ratio [OR], 3.14; 95% CI, 1.31‐7.51), experienced suffering with limited benefit from the most recent treatment (OR, 4.78; 95% CI, 1.16‐19.72), or experienced suffering from symptoms (OR, 2.91; 95% CI, 1.18‐7.16). Conclusions: Parents of children with poor‐prognosis cancer frequently make decisions based on unrealistic expectations. New strategies for effective prognosis communication are needed. Abstract : In the current study, only approximately 25% of parents of children with recurrent or refractory neuroblastoma recognize the child's poor prognosis. Parents who recognize low chances of cure appear to be more likely to prioritize quality of life over cure.